Computer-assisted stereoelectroencephalography planning: center-specific priors enhance planning - Dasgupta, Debayan; Elliott, Cameron A.; O’Keeffe, Aidan G.; Rodionov, Roman; Li, Kuo; Vakharia, Vejay N.; Mirza, Farhan A.; Tahir, M. Zubair; Tisdall, Martin M.; Miserocchi, Anna; McEvoy, Andrew W.; Ourselin, Sebastien; et al. (Frontiers in Neurology, 2025)
ObjectivesThis study aims to refine computer-assisted planning (CAP) of SEEG implantations by adding spatial constraints from prior SEEG trajectories (“Priors”) to improve safety and reduce manual adjustments, without increasing planning time.MethodsRetrospective validation based on 159 previously implanted trajectories (11 cases) planned by the clinical standard CAP and CAP constrained with spatial priors (“CAP + Priors”). Constraints included 31 target and 51 entry zones, created from 98 consecutive patients (763 implanted SEEG trajectories). Each of the 159 previously implanted trajectories was planned by two fellows, once with CAP and once with CAP + Priors, in a randomized order. The time taken to generate the initial computer-generated plan (T1) and the user-edited final plan (T2) were recorded together with the proportions of electrodes that required subsequent adjustments. Clinical implantability was assessed via a blinded review of each trajectory by five independent epilepsy neurosurgeons with expertise in SEEG implantation.ResultsExpert raters considered 88.5% of trajectories implantable, with no difference in acceptability between CAP alone and CAP + Priors (p = 0.79). Median (IQR) T1 for CAP to produce complete automated implantation was 4.6 (0.85) min vs. CAP + Priors was 6.3 (2.6) min (p = 0.03). There was no significant difference in T2 (time to complete surgeon-edited plan): CAP median (IQR) 105 (22) min, and CAP + Priors median (IQR) 96 (68) min (p = 0.92). The CAP + Priors risk score was significantly lower than that for the previously actually implanted trajectories for the 11 plans analyzed (p = 0.004), and no different from CAP alone planning. A significant reduction was observed in manual adjustments required with CAP + Priors in the cingulate gyrus.ConclusionUsing spatial priors from previous implantations enhances SEEG CAP and increases the granularity of trajectory planning. This approach facilitates more standardized planning and allows for the incorporation of experience from multiple expert centers, decreasing the risk of the resultant trajectories and reducing the proportion of trajectories that require manual planning without significantly increasing planning time.